Angucycline Glycosides from Mangrove-Derived Streptomyces diastaticus subsp. SCSIO GJ056 - Chun Gui; Yena Liu; Zhenbin Zhou; Shanwen Zhang; Yunfeng Hu; Yu-Cheng Gu; Hongbo Huang; Jianhua Ju (Marine Drugs, 2018)
Nine new angucycline glycosides designated urdamycins N1–N9 (1–9), together with two known congener urdamycins A (10) and B (11), were obtained from a mangrove-derived Streptomyces diastaticus subsp. SCSIO GJ056. The structures of new compounds were elucidated on the basis of extensive spectroscopic data analysis. The absolute configurations of 6–9 were assigned by electronic circular dichroism calculation method. Urdamycins N7 (7) and N8 (8) represent the first naturally occurring (5R, 6R)-angucycline glycosides, which are diastereomers of urdamycins N6 (6) and N9 (9), respectively.